Trends in co-morbidities and survival for in-hospital cardiac arrest –A Swedish cohort study. (March 2018) - Hjalmarsson, Patrik; Memar, Mahta; Geara, Sammy-Jo; Bouzereau, Mathilde; Allberg, Anna; Elgadi, Abdelaziz; Piscator, Eva; Djärv, Therese
Abstract: Objectives: Co-morbidities affect survival after in-hospital cardiac arrests (IHCA). The risk population for IHCA, i.e. the hospitalised patients, have a doubled increase in co-morbidities over time. A similar increase in co-morbidities among IHCAs might explain the relatively poor survival ratios despite improved care. Aim: To assess changes in the burden of baseline age-adjusted Charlson co-morbidity index (ACCI) scores among IHCAs as well as to assess its impact on survival in three time periods. Material and methods: All patients ≥18 years suffering an IHCA at Karolinska University Hospital between 1st January 2007 and 31st December 2015 were included. Data regarding the IHCA, patient characteristics, ACCI and 30 day survival were obtained from electronic patient records. Parameters included in ACCI were assessed as ICD-10 codes in the medical file at admission to hospital. The median ACCI with interquartile range (IQR) was presented per year. ACCI was categorised into low 0–2points, moderate 3–5points, high 6–8 points and very high ≥9 points. Differences in survival between 2007 and 2009 and 2010–2012 as well as 2013–2015 were stratified per ACCI category and assessed with adjusted logistic regression models and presented as Odds Ratios with 95% Confidence Intervals (OR, 95% CI). Adjustments included hospital site, sex, first rhythm, ECG-surveillance, witnessed or not, and location of the IHCA. Results: In all, 1373 patients suffered an IHCA, of whom 376 (27%) survived at least 30 days. The ACCI remained almost constant over time at median 4, IQR 3–6. Patients with low or moderate ACCI more than doubled their survival in 2013–2015 compared to 2007–2009 (adjusted OR 2.61 95% CI1.38–4.94 and OR 1.87 95% CI 1.14–3.09 respectively). Conclusion: This cohort study illuminates an almost constant burden of co-morbidities over time among patients suffering an IHCA. Further, the study highlights that 30-day survival has almost doubled from 2007 to 2009 to 2013–2015 among those with low to moderate Acc I.